2015
DOI: 10.1111/jomf.12210
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Work Absence: A Longitudinal Study of Language Impairment and Behavior Problems in Preschool Children

Abstract: Combining work and family responsibilities is challenging when children have special needs, and mothers commonly make employment-related adjustments. In this study, the authors examined associations between maternal work absence and child language impairment and behavior problems in preschool children. Questionnaire data at child age 3 years from 33,778 mothers participating in the prospective population-based Norwegian Mother and Child Cohort Study were linked to national register data on employment and long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
1
3
1
1
Order By: Relevance
“…Although we found no association with other, seemingly less severe, neurodevelopmental or behavioural problems, previous findings showed that mothers with a preschool child with language impairment had increased risk of not being employed and of taking long-term sick leaves [ 10 ]. Since our outcome, unemployment, consists of an extreme measure of maternal nonparticipation at work, we expect that only the more severe and chronic child conditions, i.e.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Although we found no association with other, seemingly less severe, neurodevelopmental or behavioural problems, previous findings showed that mothers with a preschool child with language impairment had increased risk of not being employed and of taking long-term sick leaves [ 10 ]. Since our outcome, unemployment, consists of an extreme measure of maternal nonparticipation at work, we expect that only the more severe and chronic child conditions, i.e.…”
Section: Discussioncontrasting
confidence: 95%
“…Although evidence concerning learning disabilities’ impact on maternal work participation is scarce, previous research has shown an association between children’s intellectual disability and maternal work participation [ 23 , 24 ], which may include learning problems, among other types of disorders. Concerning behaviour problems, our results are in line with findings from previous studies in toddlers and pre-schoolers to be associated with lower maternal employment [ 10 , 11 ]. Behaviour problems in early adolescents have also been shown to contribute to the multiple barriers to women’s accessing and retaining stable and quality employment, particularly in economically disadvantaged families [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, caregivers may need to miss work to deal with problems at school or to take the child to treatment. Often, excessive caregiving demands conflict with work responsibilities, leading caregivers to reduce work hours or leave their jobs [ 12 , 13 , 14 ]. In their survey of employed caregivers of children with mental health challenges, Rosenzweig and Huffstutter [ 15 ] found that many had quit a job (48%) or been terminated due to their care responsibilities (27%).…”
Section: Introductionmentioning
confidence: 99%
“…Η καθυστέρηση στην ανάπτυξη λεξιλογίου σε συνδυασμό και με άλλους παράγοντες (κοινωνικοοικονομικούς, σχέση του παιδιού με φροντιστές) φαίνεται να δημιουργεί επιπρόσθετο κίνδυνο εμφάνισης ψυχοκοινωνικών δυσκολιών, όμως η σχέση η οποία φαίνεται υπάρχει μεταξύ γλωσσικών προβλημάτων και προβλημάτων συμπεριφοράς δεν έχει ερευνηθεί επαρκώς στην προσχολική ηλικία (Beitchman & Brownlie, 2010;Carson et al, 1998;Καρούσου & Μοκαΐτη, 2018;Naerland, 2011;Nes et al, 2015). Γενικότερα στη σχετική βιβλιογραφία, λείπει η πληροφόρηση για τη συμβολή της γλωσσικής ανάπτυξης σε ότι αφορά στη συμπεριφορά των παιδιών προσχολικής ηλικίας (Bretherton et al, 2014;Stanton-Chapman et al, 2007).…”
Section: εισαγωγήunclassified